2006
DOI: 10.1007/s11524-005-9015-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hepatitis C Virus Infection on Health-Related Quality of Life in Prisoners

Abstract: Hepatitis C virus (HCV) infection in prisoners represents an important public health problem. However, there is very little information about HCV-related health-related quality of life (HRQOL). We examined the effect of HCV antibody positivity, HCV viremia, and being a prisoner on prisoners'' HRQOL. Population-based health surveys incorporating HCV screening were conducted among prisoners at New South Wales (NSW), Australia, correctional centers in 1996 and 2001. HCV antibody and HCV RNA status were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
4
21
0
Order By: Relevance
“…Following the findings by Barros et al [31], the prevalence of reported hepatitis C and HIV is prominent. Furthermore, though these diseases have increasingly become the subject of attention of both prison health policies and researchers [21], the high number of inmates with hepatitis C and HIV remains a matter of concern for public health [21, 32, 33], being the female prison population the most affected [34, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…Following the findings by Barros et al [31], the prevalence of reported hepatitis C and HIV is prominent. Furthermore, though these diseases have increasingly become the subject of attention of both prison health policies and researchers [21], the high number of inmates with hepatitis C and HIV remains a matter of concern for public health [21, 32, 33], being the female prison population the most affected [34, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…56 Although quality of life in prisoners is lower than that of the general population, hepatitis C infection has not been shown to make a significant impact. 57 This is likely because non-HCV factors override HCV-specific quality of life impairment. Furthermore, nonviral HCV-specific quality of life impairments are likely to be equally distributed between prisoners who are and who are not treated for hepatitis C infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent international and national research acknowledges that tattooing and body piercing practices exist in prisons and could be a risk for the transmission of blood borne virus infections; however due to overlapping risk behaviours such as injecting drug use it is difficult to establish the extent of the risk (Post et al, 2001;Abiona et al, 2010;Thein et al, 2006;Butler et al, 2004 Of the 102 young people who reported having at least one tattoo, 66% reported to have one or two tattoos, 26% had three or four tattoos and 9% reported to have five or more tattoos. There were no significant differences detected in the number of tattoos by gender or Aboriginality.…”
Section: Tattooing and Body Piercingmentioning
confidence: 99%